2011
DOI: 10.1038/mp.2011.131
|View full text |Cite
|
Sign up to set email alerts
|

Potential metabolite markers of schizophrenia

Abstract: Schizophrenia is a severe mental disorder that affects 0.5–1% of the population worldwide. Current diagnostic methods are based on psychiatric interviews, which are subjective in nature. The lack of disease biomarkers to support objective laboratory tests has been a long-standing bottleneck in the clinical diagnosis and evaluation of schizophrenia. Here we report a global metabolic profiling study involving 112 schizophrenic patients and 110 healthy subjects, who were divided into a training set and a test set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
190
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(216 citation statements)
references
References 54 publications
(60 reference statements)
14
190
2
4
Order By: Relevance
“…7 Similarly, the patients with dementia of Alzheimer' type and with the alcohol abuse, who showed the decrement of brain glucose utilization and the increase in acetate uptake in the brain, [31][32][33] presented with a dysregulation between CMR and CBF. 34,35 The metabolic profiling study 36 and postmortem study 37 indicated the disordered energy metabolism in the brain of schizophrenia. Brain depends exclusively on glycolysis and oxidative phosphorylation to create ATP.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, the patients with dementia of Alzheimer' type and with the alcohol abuse, who showed the decrement of brain glucose utilization and the increase in acetate uptake in the brain, [31][32][33] presented with a dysregulation between CMR and CBF. 34,35 The metabolic profiling study 36 and postmortem study 37 indicated the disordered energy metabolism in the brain of schizophrenia. Brain depends exclusively on glycolysis and oxidative phosphorylation to create ATP.…”
Section: Discussionmentioning
confidence: 99%
“…Providing a further link to mitochondrial dysfunction, we identified decreased levels of pyruvate kinase and we validated this finding at the functional level using pyruvate assay. Altered pyruvate levels were identified in a recent global metabolic profiling study involving 112 schizophrenic patients and 110 healthy subjects, and this was then used in a potential novel diagnostic panel for SCZ (Yang et al, 2013). In addition, converging evidence suggests that malfunction of energy supply through the brain glycolytic and TCA cycles is a causative factor of SCZ (Hazlett et al, 2004;Olsen et al, 2008).…”
Section: Biological Functions P-values Proteins Biological Functions mentioning
confidence: 99%
“…22,23 A few metabolomic studies of autism have recently been carried out using different techniques in a variety of biospecimens. A urine study using a 1 H nuclear magnetic resonance (NMR) spectroscopy method has shown an elevated level of taurine and decreased glutamate in urine samples of patients with autism.…”
Section: J Psychiatry Neurosci 2016;41(1)mentioning
confidence: 99%